Ripping off the Band-Aid: Scrutiny Bundling in the Wake of Social Disapproval - Titus, Varkey K.; Parker, Owen; Bass, A. Erin (Academy of Management Journal, 2018)
Activities that hazard the possibility of increased scrutiny are an unavoidable reality for many firms. While managers may face the need to engage in these activities, there is little research on when managers decide to do so. Existing theoretical perspectives on status quo deviations have not sufficiently addressed how managers order the firm’s essential activities that differ primarily in terms of the scrutiny those activities engender. Drawing from concepts in the accounting and political science literatures, we advance a “scrutiny-bundling” perspective that suggests that firms engage in scrutiny-hazarding action in the wake of social disapproval, assessed in this study via negative media coverage. We further theorize that a strong linkage between the focus of media coverage and the specific scrutiny-hazarding action exacerbates this relationship. We then contend that managers at firms that are either large in size or that perform well relative to their aspirations are less sensitive to social disapproval, and are therefore less likely to engage in scrutiny bundling. We test our hypotheses on a sample of 100 firms in the upstream petroleum industry and find general support for our theories.